ChemInform Abstract: Four New Steroidal Glycosides, Protolinckiosides A—D, from the Starfish Protoreaster lincki. Issue 52 (6th December 2016) - Malyarenko, Timofey V.; Kicha, Alla A.; Kalinovsky, Anatoly I.; Ivanchina, Natalia V.; Popov, Roman S.; Pislyagin, Evgeny A.; Menchinskaya, Ekaterina S.; Padmakumar, Krishna Pillai; Stonik, Valentin A.
Abstract: [isolation, structure elucidation and bioactivity of the title steroidal glycosides, cf.